A SOLAR POWERED MINI SMART E-PODIUM WITH A WIRELESS LECTURE TRANSMITTER - VICTOR O. MATTHEWS; STANLEY UZAIRUE IDIAKE; ETINOSA NOMA-OSAGHAE (International Journal of Innovations in Engineering Research and Technology, 2021)
To get an effective learning experience, conscious work on the part of the teacher and students is required. The purpose of this article is to present the design and construction of a solar powered mini classroom/corporate e-podium. This paper describes how the proposed e-podium exactly mimics ideas and perceptions about the ways lecturers and students work with the podium within the classroom setting to deliver better educational experiences. The e-podium has software that allows each lecture to be transmitted live to the audience via a wireless link. Any mobile device or laptop can be on the same page with the lecturer, especially in very large classroom settings.